2016
DOI: 10.3889/oamjms.2016.027
|View full text |Cite
|
Sign up to set email alerts
|

3D Finite Element Study on: Bar Splinted Implants Supporting Partial Denture in the Reconstructed Mandible

Abstract: AIM:This study aimed to estimate the stress patterns induced by the masticatory loads on a removable prosthesis supported and retained by bar splinted implants placed in the reconstructed mandible with two different clip materials and without clip, in the fibula-jaw bone and prosthesis using finite element analysis.METHODS:Two 3D finite element models were constructed, that models components were modeled on commercial CAD/CAM software then assembled into finite element package. Vertical loads were applied simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…It seems, therefore, that the risk of loosening or even damage to these elements is greater than the disintegration of the implant or peri-implantitis [ 40 , 41 ]. The conducted research confirmed the reports of other authors that the greatest load occurs in the distal parts of the bar retention [ 42 , 43 ]. Stress concentration, however, within the clips results from their shape.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It seems, therefore, that the risk of loosening or even damage to these elements is greater than the disintegration of the implant or peri-implantitis [ 40 , 41 ]. The conducted research confirmed the reports of other authors that the greatest load occurs in the distal parts of the bar retention [ 42 , 43 ]. Stress concentration, however, within the clips results from their shape.…”
Section: Discussionsupporting
confidence: 89%
“…The studies presented in this paper show the interdisciplinary character of today’s prosthetics. FEA is applied by a growing number of researchers [ 24 , 38 , 43 , 46 ]. Advances in virtual engineering enable making computer simulations in concrete and stable conditions, which helps avoid mistakes in experimental studies.…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of the loads and stresses in dental structures attached to the jaw with the help of implants has been studied in many works, and general approaches to such problems can be divided into three global areas. The first direction is based on analytical methods [ 75 , 76 , 77 , 78 , 79 ], the works of the second direction are based on the finite element method and the setting of a virtual experiment [ 80 , 81 , 82 , 83 , 84 ], and the third direction uses the means of model and field experiments [ 85 , 86 , 87 , 88 , 89 ]. Our article develops the first analytical line of research.…”
Section: Discussionmentioning
confidence: 99%
“…Bar attachment was the one of choice in this study. It was stated that dental implants allow better stress distribution and less prosthetic maintenance in comparison to non-splinted implants (9) . Cone beam radiograph was used to assess alveolar bone height and its loss around implants.…”
Section: Discussionmentioning
confidence: 99%